The prevalence of gastrointestinal symptoms among patients with COVID‐19 and the effect on the severity of the disease. Issue 6 (18th September 2020) - Sulaiman, Tharwat; Algharawi, Ali A; Idrees, Marwan; Alzaidy, Rafid H; Faris, Kawthar; Cullingford, Graham; Rasheed, Jawad
Abstract: Background and Aim: COVID‐19 is a new pandemic disease recognized by the World Health Organization. It mainly affects the respiratory system, but it can also affect other systems. The gastrointestinal system has been found to be affected in many patients. This study investigated the COVID‐19‐related gastrointestinal manifestations and the effect of gastrointestinal involvement on the course and outcome of the disease. Methods: This was a retrospective descriptive study conducted on 140 COVID‐19 polymerase chain reaction‐positive symptomatic individuals admitted to Al‐Shafa Hospital – Medical City Complex in Baghdad, Iraq during the period 2 March 2020 to 12 May 2020. Demographic data and clinical presentation and laboratory data were extracted from the case sheets of the patients and were also obtained from direct communication with the patients, their families, and medical staff. Results: Gastrointestinal (GI) symptoms alone were detected in 23.6% of the patients; 44.3% of the patients presented with only respiratory symptoms, and 32.1% presented with both respiratory and GI symptoms. Patients with only GI symptoms had less severe disease compared with those who had both GI and respiratory symptoms, who had more severe disease with higher mortality. Overall mortality was 8.6%, with no mortality in the GI symptoms alone group. The highest severity and mortality were in patients with both GI and respiratory symptoms (48.39 and 13.33%, respectively). Conclusions: COVID‐19‐related gastrointestinal symptoms are common, and their presence alone carries a better prognosis, but their presence with respiratory symptoms is associated with higher morbidity and mortality. Abstract : This study investigated the COVID‐19‐related gastrointestinal manifestations and the effect of gastrointestinal involvement on the course and outcome of the disease. We concluded that COVID‐19‐related gastrointestinal symptoms are common, and their presence alone carries a better prognosis, but their presence with respiratory symptoms is associated with higher morbidity and mortality.